2013
DOI: 10.1128/jvi.00714-13
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus Nonstructural C Protein Modulates Viral RNA Polymerase Activity by Interacting with Host Protein SHCBP1

Abstract: cMost viruses possess strategies to circumvent host immune responses. The measles virus (MV) nonstructural C protein suppresses the interferon response, thereby allowing efficient viral growth, but its detailed mechanism has been unknown. We identified Shc Src homology 2 domain-binding protein 1 (SHCBP1) as one of the host proteins interacting with the C protein. Knockdown of SHCBP1 using a short-hairpin RNA greatly reduced MV growth. SHCBP1 was found to be required for viral RNA synthesis in the minigenome as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 58 publications
3
50
1
Order By: Relevance
“…This specific localization phenomenon was not observed in SHCBP1-siRNA Cells (Asano et al, 2013) .The research findings indicated that SHCBP1 might be play an important role in encouraging G0/G1 phase into S phase in cell cycle changes. SHCBP1 was found to be required for viral RNA synthesis and might be exploited as a target of anti-viral compounds (Ito et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This specific localization phenomenon was not observed in SHCBP1-siRNA Cells (Asano et al, 2013) .The research findings indicated that SHCBP1 might be play an important role in encouraging G0/G1 phase into S phase in cell cycle changes. SHCBP1 was found to be required for viral RNA synthesis and might be exploited as a target of anti-viral compounds (Ito et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this case the mechanism proposed involves the viral C protein because C-deficient virus, but not the wild type, strikingly induces SGs [39]. Although measles C protein has diverse functions during infection, including modulation of viral polymerase activity and inhibition of IFN production [40], the molecular machinery for SG inhibition remains to be determined. Figure 2.…”
Section: Inhibition Of Sg Formation By Viruses: An Antiviral Role Formentioning
confidence: 99%
“…The V protein interferes with activation of RNA helicase MDA5 by preventing PP1-mediated dephosphorylation of the CARD domain and IjB kinase a to interfere with IFN induction (27,126,132) and with Stat1/2 to inhibit IFN signaling (19,140). The C protein downregulates viral RNA synthesis and production of defective interfering (DI) RNAs to decrease virus detection intracellularly (59,106,121,133). MeV is an antigenically monotypic virus, with 24 genotypes recognized based on the sequence of the C terminus of the N gene (148).…”
Section: Introductionmentioning
confidence: 99%